Fostering mental health at work: the butterfly effect of management behaviors. Issue 13 (27th July 2022) - Lecours, Alexandra; St-Hilaire, France; Daneau, Patrice
Abstract: With the growing number of work-related mental health problems occurring worldwide, a call for all stakeholders to contribute to improving these problems has emerged. Managers' behaviors may act as a resource to promote the involvement of employees to foster mental health at work through their behaviors. This study aims to identify the behaviors of managers supporting the behaviors of employees fostering mental health at work. Following a qualitative research design, data were collected through interviews ( n  = 22) and analyzed using a template analysis strategy. The results reveal 20 concrete, specific and fairly simple behaviors that managers may adopt to support the involvement of their employees in behaviors fostering mental health at work. For example, consulting employees, providing room for mistakes and organizing social activities are behaviors managers may adopt to support the engagement of employees in behaviors fostering mental health at work. According to social exchange theory, the results of this study propose levers to implement a favorable context in which the behaviors of managers and those of employees interact. Given the potential influence of managers' behaviors on mental health at work, including this new knowledge in manager training would be judicious to foster shared responsibility for mental health at work.